Variable HOF-derived carbon-coated cobalt phosphide for electrocatalytic oxygen evolution. (30th August 2022) - Guo, Yuanyuan; Sun, Qiuhong; Huang, Qi; Hu, Yue; Su, Kongzhao; Li, Ting-Ting; Huang, Shaoming; Qian, Jinjie
Abstract: A structural and morphological transformation of a hydrogen-bonded organic framework (HOF) based on 1, 3, 5-benzentricarboxylic acid (H3 BTC) is observed. With the introduction of metal cations, especially Co(II) ion, these weaker hydrogen bonds linked in this bulk HOF of BTC can be easily broken to obtain the ultrathin wire-shaped product, denoted as Co-Fiber . That is mainly for the reason that the divalent cobalt ions with modest polarity exhibit moderate disturbance and destruction to H-bonding networks. Following calcination and phosphatization, abundant HOF-derived porous carbon-coated CoP particles in CoP/NCNT/PC inherit the morphology of Co-Fiber and endow with in-situ formed N-doped multi-walled carbon nanotubes. Initial electrochemical activation of the CoP/NCNT/PC catalyst promotes the formation of the electrocatalytically active species of cobalt oxyhydroxide for efficient oxygen evolution reaction (OER) in 1.0 M KOH aqueous solution. The obtained CoP/NCNT/PC composite exhibits an outstanding OER performance with the low overpotential of 282 mV at 10 mA cm −2, the relatively small Tafel value (103.7 mV dec −1 ), and the long-term durability remaining 90.5% over 10 h. The reasonable and facile method to synthesize low-cost, efficient and robust CoP/NCNT/PC shows great potential to substitute noble-metal based electrocatalysts for OER. Meanwhile, it will provide a new way for the application of HOF-derived carbon nanomaterials in the new energy field. Graphical abstract: Image 1 Highlights: A structural and morphological change of a hydrogen-bonded organic framework is observed. Divalent metal ions show moderate disturbance and destruction to H-bonding networks. HOF-derived carbon-coated CoP particles exhibit a satisfactory oxygen evolution.